AESTHETIC IMPROVEMENT IN ONE VISIT PERIODONTAL PLASTIC SURGERY USING SCALPEL AND LASER SURGICAL TECHNIQUE (CASE REPORT) - Nabilah; Vincensia Marina Karina (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: A charming smile is formed from good harmonization of teeth and gums. Short teeth clinical crown, dark gingival color, diastema between the maxillary central incisors can interfere the aesthetic of the smile. This case report aims to describe the treatment of periodontal plastic surgery in form of aesthetic crown lengthening, gingival depigmentation and frenectomy to improve function and aesthetic in one visit using scalpel and laser. Case: A 23 year old male patient complained that the maxillary front teeth spaced, short and small, and the gum of the upper jaw is dark, which caused aesthetic discomfort. Objective examination showed high frenal attachment reaching the interdental papilla to palatal, diastema of the maxillary central incisors, short clinical crown and brownish maxillary gingiva. aberrant frenum labialis superior, altered passive eruption and gingival hyperpigmentation diagnoses was made in this case. Case Treatment: Aesthetic crown lengthening treatment with scalpel, gingival depigmentation using scrapping technique and frenectomy using combination of laser and scalpel surgical technique was carried out in one visit. Discussions: The advantages performing three periodontal plastic surgeries in one visit is require just once preparation of surgical materials and instruments, once surgical trauma, once prescription and less number of control visits. Conclusions and Suggestions: Treatment of crown lengthening, gingival depigmentation and frenectomy in one visit are considered effective and efficient based on time, trauma, and costs required. The periodontal plastic surgery technique can be choosing based on clinical finding on patient, patient’s needed and clinical skills of operator.